Modulating immune response for the prevention and treatment of type 1 diabetes - Vohidova, Dilrasbonu; Desai, Prasi; Moreno Lozano, Alvaro; Veiseh, Omid (Frontiers in Immunology, 2026)
In type 1 diabetes (T1D), chronic autoimmune responses lead to the destruction of β-cells in pancreatic islets. As more of the β-cell mass is destroyed, the disease progresses, resulting in insulin deficiency. Recent discoveries uncovering the mechanisms behind the autoimmune attack on β-cells have allowed for a better understanding of the development of the disease and categorizing it into stages of progression. Further, FDA approval of the first drug for the prevention of T1D demonstrated the potential for early intervention therapies. Meanwhile, for patients whose β-cell mass is fully destroyed, islet transplantation has been shown to achieve long-term insulin independence. However, this procedure requires lifelong immunosuppression, which can increase the risk of infections and malignancies. Here, we will review recent advances in immunomodulation approaches for the prevention of type 1 diabetes and strategies for islet cell replacement. First, we introduce the pathogenesis of T1D and the stages of the disease that require different immunomodulatory approaches. Then, we will discuss current immunotherapies for the prevention of T1D, highlighting strategies such as antigen-specific, immune blockade, and cell-based therapies, which aim to stop autoimmune attack for patients at early stages of T1D. Afterwards, we discuss advancement for islet replacement approaches, highlighting islet engineering, device encapsulation, and immunomodulatory biomaterials, which aim to prolong the survival of transplanted islets and minimize the need for immunosuppression. We expect this review to provide a comprehensive understanding of current advances in immunomodulatory therapies for T1D.